Donde surgen las sombras Premio Gran Angular 2006 - Lozano Garbala, David 1974- (Gran angular, 2006)
When Alex disappears the same day that three people are brutally murdered, his friends join forces with the police to search for him, leading them to suspect a sinister, underground cult